Mapping of the production of the graduate program in mathematics education of UFOP - Viana, Marger da Conceição Ventura; Amorim, Keren Ingrid (Seven Editora, 2023)
Considering that the disciplines have a history, are constantly evolving, and, to remain, must be updated, this work is justified. Thus, it is presented, from a consistent perspective, a study of the History of Mathematics Education whose objective is to carry out a mapping, of the creation until 2019, of the production of the Graduate Program in Mathematics Education of the Federal University of Ouro Preto (PPGEDMAT-UFOP), that is, one hundred and fourteen dissertations and the corresponding educational products. For this, the researchers took as reference the areas established by the National Council for Scientific and Technological Development (CNPq) and then made refinements with categorizations, because, in History, the acts of separating and joining are the first steps for the production of documents. It was possible to point out a predominance of studies related to High School, the Final Years of Elementary School, and Higher Education (face-to-face). As for the themes, the predominance of Teacher Training in Mathematics, Geometry, and Modeling-Problem Solving, indicates a trend of research carried out or in progress. Therefore, the tables that gather data obtained complement the answers to the research question. DOI:https://doi.org/ 10.56238/devopinterscie-210